PLA2G6-Associated Neurodegeneration (PLAN): Review of Clinical Phenotypes and Genotypes - Guo, Yu-pei; Tang, Bei-sha; Guo, Ji-feng (Frontiers in Neurology, 2018)
Phospholipase A2 group VI (PLA2G6)-associated neurodegeneration (PLAN) includes a series of neurodegenerative diseases that result from the mutations in PLA2G6. PLAN has genetic and clinical heterogeneity, with different mutation sites, mutation types and ethnicities and its clinical phenotype is different. The clinical phenotypes and genotypes of PLAN are closely intertwined and vary widely. PLA2G6 encodes a group of VIA calcium-independent phospholipase A2 proteins (iPLA2β), an enzyme involved in lipid metabolism. According to the age of onset and progressive clinical features, PLAN can be classified into the following subtypes: infantile neuroaxonal dystrophy (INAD), atypical neuroaxonal dystrophy (ANAD) and parkinsonian syndrome which contains adult onset dystonia parkinsonism (DP) and autosomal recessive early-onset parkinsonism (AREP). In this review, we present an overview of PLA2G6-associated neurodegeneration in the context of current research.